Constrast-enhanced computed tomography radiomics predicts CD27 expression and clinical prognosis in head and neck squamous cell carcinoma - Wang, Fang; Zhang, Wenhao; Chai, Ying; Wang, Hanshao; Liu, Zhonglong; He, Yue (Frontiers in Immunology, 2022)
Objective: This study aimed to construct a radiomics model that predicts the expression level of CD27 in patients with head and neck squamous cell carcinoma (HNSCC). Materials and methods: The genomic data and corresponding enhanced computed tomography (CT) images of patients with HNSCC were downloaded from the Cancer Genome Atlas and Cancer Imaging Archive for prognostic analysis, image feature extraction, and model construction. We explored the potential molecular mechanisms underlying the CD27 expression and its relationship with the immune microenvironment and predicted the mRNA expression of CD27 in HNSCC tissues. Using non-invasive, CT-based radiomics technology, we generated a radiomics model and evaluated its correlation with the related genes and prognosis. Results and conclusion: The expression level of CD27 in HNSCC may significantly influence the prognosis of patients with HNSCC. By using enhanced CT, radiomics is potentially effective in predicting the expression level of CD27.